Comparative efficacy of indacaterol in chronic obstructive pulmonary disease - Ribeiro, Marcos (Dove Medical Press, 2012)
Long-acting bronchodilators have been shown to improve multiple clinical outcomes in chronic obstructive pulmonary disease (COPD) including lung function, symptoms, dyspnea, quality of life, and exacerbations. Indacaterol is a novel, inhaled, long-acting β2-agonist providing 24-hour bronchodilation with once-daily dosing. It is currently approved for the maintenance treatment of COPD to be administered as 150 or 300 μg once-daily doses as licensed in many countries and 75 μg as licensed in the US by means of a single-dose dry powder inhaler. The data from clinical development support a favorable safety and tolerability profile within the β2-agonist drug class, with no relevant issues identified. Current evidence indicates that indacaterol is suitable for use as first-line monotherapy in COPD patients with moderate disease (Global Initiative for Chronic Obstructive Lung Disease [GOLD] stage II) and beyond that do not require an inhaled corticosteroid (ICS) as per GOLD guidelines, or in combination with an ICS in severe or very severe patients with repeated exacerbations. Data from trials with the novel once-daily β2-agonist, indacaterol, indicate superior bronchodilation and clinical efficacy over twice-daily long-acting β2-agonists and at least equipotent bronchodilation as once-daily tiotropium. Bronchodilators are central in the symptomatic management of COPD. It is likely that once-daily dosing of a bronchodilator would be a significant convenience and probably a compliance-enhancing advantage, leading to improved overall clinical outcomes in patients with COPD.